Increasing participation in preschool: Evidence from a default enrollment policy - Caroline King Barnard Hall; Erica Lindahl; Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2025)
While all children in Sweden are entitled to free, universal preschool from age 3, enrollment rates for children with an immigrant background - and especially for those in newly-arrived families - remain well below the 95 percent national average. At the same time, studies suggest that these children have particularly high returns from preschool attendance. Thus, policies that increase preschool enrollment among children with an immigrant background have potential to improve long-term educational and labor market outcomes and narrow the gap to natives. We evaluate a reform in 2023 that required municipalities to offer preschool slots to 3-5-year-olds in newly-arrived immigrant families without the parents needing to apply - so-called automatic offers. Using a difference-in-differences specification, we compare next-year enrollment rates for currently non-enrolled children in newly-arrived families and other families and find that the policy substantially increased preschool enrollment. Our results suggest that administrative hurdles prevent some immigrant families from enrolling their children and that simplifying the application process is an effective policy tool for increasing preschool participation in this group.
Keywords: I24; I28; 330; preschool participation; foreign background; default enrollment